Marwiyyāt al-Muḥaddiśīn al-Indūnisiyyīn li al-Arbaʻiniyāt: Dirāsah ʻan Mu᾽allafāt Nawawy al-Bantany, wa Maḥfūẓ al-Termasy wa Mukhtār ibn ʻAtārid: Narrations of Indonesian Hadith Scholars for the al-Arbaʻiniyāt: Study of the Works of Nawawy al-Bantany, Maḥfūẓ al-Termasy, and Mukhtār ibn ʻAtārid - Daud Rasyid (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2021)
(Abstract) This article analyzes hadith science works of Indonesian Muslim scholars. Being the largest Muslim country, Indonesian scholars who settled in al-Haramayn in 13th H, have more significant works than other Arab region scholars. One of it is Kitab “Arba`īn” that compiled forty ḥadīth about life. It has a simple style, easy to remember, unconvoluted, and does not contain different schools of thought. The era’s leading figures who wrote about the Arba`īn and its explanation (sharah) of famous scholar’s works, are Kiyai Nawawi from Banten, Kyai Mahfūzh from Termas, Mukhtar `Atorid from Bogor, Syekh Yasin from Padang. There is also the book Arba`īn on forty ḥadīth from forty books of forty sheikhs in forty cities. This study’s main data is collected from the works of Nawawi Banten on Imām Suyūti’s “Tanqīḥ qaul al-hathīth bi syaraḥ lubāb al-ḥadīth”. In this article, the author also compares the mentioned scholar works with other similar woks then presented analysis based on the Ḥadīth knowledge. Keywords : Narration, The Prophet saying, Ḥadīth Scholar, Indonesian `Ulamā, Arba`īn ملخص : يتناول هذا المقال مؤلفات العلماء الإندونيسيين المفيمين ببلد الحرمين في القرن الثالث عشر من الهجرة ، في علم الحديث خاصة . كان لهم دور لا يقل عن دور علماء العرب حينذاك حيث كان لهم مؤلفات متميزة في فنون مختلفة وتنوعت مؤلفاتهم في الحديث منها تأليف الأربعينيات وهو جمع أربعين حديثا من مصادر مختلفة وموضوعات متنوعة. ولعل الهدف منه تسهيل المجتمع العام للرجوع إلى مصادر دينهم دون الخوض في الخلافات ، والتعصب المذهبي. وهذا النمط يساعد المبتدئين في التفقه في دينهم ، وكان أمثال نووي البنتني ، ومحفوظ الترمسي ومختار عطارد البوغوري وياسين الفاداني من بين الرموز المشهورة. ومن بين أعمالهم شرح الأربعين وجمع أربعين حديثا من أربعين كتابا من أربعين شيخا من أربعين بلدا. وكان مرجع هذا البحث مؤلفات هؤلاء مثل كتاب (تنقيح القول الحثيث شرح لباب الحديث للسيوطي) للنووي ، وكتابي (المنحة الخيرية) و(الخلعة الفكرية) للترمسي و(أربعين) مختار بن عطارد. وعمل الكاتب هنا مقارنة تلك المؤلفات بالمؤلفات المشابهة وشيئ من التحليل العلمي المناسب. الكلمات المفتاحية : الروايات ، الحديث ، المحدثون ، الإندونيسيون ، الأربعين .